The Using Results of OER Mobile Application to Enhance 21st Century Skills in Information Media and Technology Skills for Humanities and Social Sciences - Kemmanat Mingsiritham (International Journal of Interactive Mobile Technologies, 2020)
The purpose of this research was to study the using results of OER mobile application to enhance 21st century skills in information media and technology skills for humanities and social sciences learners. The sample included 33 students who studied in an autonomous university in the Humanities and Social Sciences field. Research instruments consisted of self-assessment form before and after studying, behavior observation form, and assignment evaluation form. Data were analyzed by using mean, standard deviation, dependent t-test, and one way repeated measure. The results showed that information, media and technology skills had average scores after studying higher than before studying with statistical significance at the level of .05 (t = 17.382, p = .000). Students had learning behavior with OER mobile application at very high level (M = 4.52, SD = .26). The analysis of one way repeated measure of assignment evaluation in each period (week 2, week 4, week 6) showed statistically significant at the .05 level.